Examining Google Classroom-assisted blended learning in Indonesian EFL grammar classes - Nur Muthmainnah (Erudita: Journal of English Language Teaching, 2022)
The present study aims to examine the effectiveness of Google Classroom-assisted blended learning in two EFL grammar classes. It investigates the difference between EFL students’ grammar mastery applying blended learning and discussion method. Framed in experimental research, this study recruited 52 EFL student teachers in an Indonesian university to participate. Data were garnered through multiple choice tests. Study findings reveal that the significance value of paired sample t-test was 0.00 < 0.05, showing that there was significant influence of blended learning toward the EFL students’ grammar mastery. The significance value of t-test (2.029) > t-table (0.2732) indicates that there was a difference in the students’ grammar mastery after giving treatment in experimental and control groups. The N-gain value was 0.1164 > 0.7, proving that Google Classroom-aided blended learning was effective to foster the students’ grammar mastery. Since the t-test (2.029) > t-table (0.2732), H1 was accepted and H0 was rejected. This means that Google Classroom-assisted blended learning gave a positive impact on the students’ grammar mastery. This study concludes with some empirical evidence that Google Classroom-mediated blended learning is promoted to be an innovative learning management system in EFL classes to boost students’ grammar mastery.